Financial Integration, Financial Dependence and Employment Growth - Gur, Nurullah (International Journal of Economics and Financial Issues, 2015)
In this paper we analyse the effect of financial integration on employment growth. The results show that financial integration increases employment growth relatively more in financially dependent industries when we use de jure measure of financial integration. Using de facto measures of financial integration, we find that international portfolio equity investments and foreign direct investments increase employment growth disproportionately more in industries that are heavily dependent on external finance. But, external debt has no significant effect on employment growth. We also find that the positive effect of financial integration on employment growth disappears in countries with underdeveloped financial system and extractive institutions. Keywords: Financial integration; external finance; employment JEL Classifications: E24; G15; G28, O16